Mississippi Workers World Party contingent - Sahl, Ted (photographer):::Creator::::::::::::
Photograph shows two men holding a banner that reads, "Stonewall, [Means] fight back, [Smash] lesbian & gay oppression. Carter and Congress: we demand lesbian and gay rights now! YAWF Mississippi Workers World Party". Other marchers follow the banner carriers during the National March on Washington for Lesbian and Gay Rights.